Antimicrobial or Subantimicrobial Antibiotic Therapy as an Adjunct to the Nonsurgical Periodontal Treatment: A Meta-Analysis. (22nd October 2012) - Moreno Villagrana, Ana Patricia; Gómez Clavel, José Francisco
Abstract : The use of antibiotics in nonsurgical periodontal treatment is indicated in cases in which scaling and root planing present important limitations. However, their use is controversial due to the secondary effects associated with them and the disagreements regarding their prescription. The aim of this study is to determine the effectiveness of systemic antibiotics in the management of aggressive and chronic periodontitis. The study was based on a search of randomized, controlled clinical trials. Common data were concentrated and evaluated by means of an analysis of variance (ANOVA), and a meta-analysis of the results was performed. The meta-analysis (P < 0.05, 95% confidence interval, post hoc Bonferroni) determined that the supplementation of nonsurgical periodontal therapy with a systemic antibiotic treatment—amoxicillin with clavulanic acid and metronidazole or subantimicrobial dose doxycycline—provides statistically significant results in patients with aggressive or chronic periodontitis under periodontal treatment, whilst increasing the clinical attachment level of the gingiva and reducing periodontal probing depth.